IMPLEMENTASI PERATURAN BUPATI LIMA PULUH KOTA NOMOR 37 TAHUN 2017 TENTANG PEDOMAN PENYELENGGARAAN PENANGANAN PENYANDANG MASALAH KESEJAHTERAAN SOSIAL (PMKS) ( Studi Kasus Di Kecamatan Bukik Barisan ) - Bionti, Gilang Dasoma; HZ, Evi Deliana; Zulhidayat, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Social welfare development is an embodiment of efforts to achieve the nation's goalsmandated in the 1945 Republic of Indonesia Constitution. The emergence of the PMKS problem isstill a complex problem in every region in Indonesia. These social welfare problems show that thereare citizens whose rights to their basic needs have not been fulfilled properly because they have notreceived services from the state. Efforts to overcome PMKS are a priority that need to beimplemented in every development program implementation. In this regard, the local government ofLimapuluh Kota Regency has stipulated Limapuluh Kota Regent Regulation Number 37 of 2017concerning Guidelines for Implementing Handling of People with Social Welfare Problems(PMKS). In this writing the author focuses on the implementation of the Fifty Cities RegentRegulation Number 37 of 2017. The purpose of writing this thesis is; First, to find out how toimplement of the Fifty Cities Regent Regulation Number 37 of 2017 in Bukik Barisan District,Second, to find out the obstacles in implementing of the Fifty Cities Regent Regulation Number 37of 2017 in Bukik Barisan District, Third, to find out efforts In Overcoming Obstacles inImplementing of the Fifty Cities Regent Regulation Number 37 of 2017 in Bukik Barisan District.Based on the problems posed, the type of legal research used by researchers is empirical juridicalresearch or sociological legal research. The method used in this research is a survey methodbecause in this research the author went directly to the research location. The nature of thisresearch is descriptive, namely research that prioritizes observation of symptoms, events andcurrent events.From the results of research on the problem, there are three main things that can beconcluded. First, the implementation of handling PMKS in Bukik Barisan District is not going well.Second, obstacles in implementing PMKS handling are the lack of budget for carrying out PMKShandling programs, inaccurate validation of PMKS data, and errors in handling PMKS. Third,efforts to overcome obstacles to the implementation of handling PMKS, namely reviewing thedetermination of the Social Service budget, emphasizing the Social Service in Data Validation, andimplementing preventive efforts for several PMKS categories. The author's suggestions, First,Recommend that the Regent and DPRD in determining the Social Service budget be adjusted tocurrent conditions. Second, Suggest that the Regional Government and Social Service be moreactive and thorough in validating data and be more selective in selecting humanresources/apparatus in the Social Service. Third, recommend that every government agencyauthorized to administer social welfare coordinate with each other and work together as well aspossible in handling PMKS.Keywords: Implementation - Treatment - Persons - Problems - Welfare - Social